Fifty Years of Catholic-Pentecostal Dialogue, 1972–2022: A Pentecostal Assessment - Robeck, Cecil M. (Pneuma, 2022)
This article offers a sweeping view of the first fifty years of the International Roman Catholic–Pentecostal Dialogue, from the perspective of an historian who has participated in this ongoing discussion for the past thirty-seven years. While the first two rounds of dialogue were especially difficult because of the political disputes between the then Assemblies of God General Superintendent, Thomas F. Zimmerman, and David du Plessis, the former General Secretary of the Pentecostal World Conference, the Dialogue has survived and produced six major studies so far, with a seventh round that has resumed after COVID-19 in July 2022. Today, this ecumenical dialogue is the oldest and most widely accepted in the world that features Pentecostals. The article explains some of the difficulties participants have faced, challenges they have overcome, and it explains how the dialogue has opened doors for further communication between Catholics and Pentecostals. It concludes with the recognition that the dialogue has contributed to problem solving and has helped to open the path towards the establishment of the Christian Unity Commission of the Pentecostal World Fellowship.